Unity of Muslims: a reflection on its materialization - Khan, Israr Ahmad (2016)
Theoretically, Muslim scholars, scientists, politicians, economists, authors, media persons, orators, educationists, businessmen, teachers, students, and general masses feel very much concerned about the horrifying scenario of disunity among Muslims. This concern inspires them all to do something to bring back the lost unity among Muslims. Books have been written on this issue; researches have been conducted to identify the nature of this problem; speeches have been delivered on how to resolve this entanglement; deliberations have been made over this predicament; and conferences have been organized to address the pros and cons of harmony among Muslims. Yet, it appears that the dream of Muslim unity still remains elusive. As for the differences among Muslims from various angles, political, social, intellectual, cultural, religious, doctrinal, and philosophical, there seems to be no way to remove them totally thus converting all Muslims into one single entity. This paper attempts to suggest some practical ways to infuse the spirit of unity among Muslims, without challenging their respective creeds and thoughts. The framework for the deliberation over this issue is four dimensional: the Qur’an, the Hadith, Scholars’ views, and independent reasoning (tadabbur).